Chitosan-based NPK nanostructure for reducing synthetic NPK fertilizers and improving rice productivity and nutritional indices - Elshayb, Omnia M.; Ghazy, Hassnaa A.; Wissa, Mariam T.; Farroh, Khaled Y.; Wasonga, Daniel O.; Seleiman, Mahmoud F. (Frontiers in Sustainable Food Systems, 2024)
Researchers have repeatedly emphasized how urgently we musthave to decrease the massive nitrogen fertilizer consumption to support agricultural productivity and maintain a sustainable ecosystem. Using chitosan (CS) as a carrier for slow release is considered a potential tool for reducing synthetic fertilizer and improving crop productivity. Therefore, two field experiments were conducted arranged in a randomized complete block design to investigate the effects of seven treatments including synthetic fertilizer and exogenous application of chitosan-based NPK nanostructure (Ch/NPs-NPK) on growth, productivity, and nutrient uptake traits of rice as a worldwide strategy crop during 2022 and 2023 growing seasons. The experimental treatments were: T1= full recommended synthetic NPK (recommended urea, superphosphate, potassium sulfate; control treatment) , T2= 70% of T1 + Ch/NPs-NPK 100 ppm, T3= 70% of T1+ Ch/NPs-NPK 200 ppm, T4= 70% of T1+ Ch/NPs-NPK 300 ppm, T5= 30% of T1+ Ch/NPs-NPK 100 ppm, T6= 30% of T1+ Ch/NPs-NPK 200 ppm, and T7= 30% of T1 + Ch/NPs-NPK 300 ppm. The results revealed that T4 (i.e., 70% of recommended NPK+ Ch/NPs-NPK 300 ppm) and T1 (full recommended synthetic NPK) resulted in the highest and most significant growth and yield traits of rice as well as nutrient grain contents compared to other treatments. Therefore, combining 70% of recommended NPK with Ch/NPs-NPK 300 ppm as an exogenous application can be a smart choice for reducing synthetic NPK fertilizers by 30% in paddy fields without producing a significant decline in terms of growth, yield characteristics, or nutrient grain contents when applying the full recommended synthetic NPK.